1996
DOI: 10.1192/pb.20.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Observations from community care for serious mental illness during a controlled study

Abstract: A controlled study of community care in serious mental illness (SMI) was carried out. Patients with SMI were randomised to have hospital care or be looked after by a community psychiatric care team in a Daily Living Programme (DIP). The day-to-day work of a clinical team with the difficulties encountered in delivering community psychiatric care in an inner city is described. There were seven deaths from self-harm during the 45-month study. One DIP patient committed homicide. An ordeal by media following this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Several studies in the 1990s reported high levels of ‘burn-out’ among community mental health team (CMHT) staff, although paradoxically associated with relatively good job satisfaction (Fagin et al , 1995; Prosser et al , 1996; Onyett et al , 1997; Wykes et al , 1997). Some authors have argued that staff delivering intensive community care to severely ill client groups are very susceptible to burn-out, threatening the sustainability of this model (Dedman, 1993; Connolly et al , 1996). However, assertive outreach team staff may also find the work particularly rewarding.…”
mentioning
confidence: 99%
“…Several studies in the 1990s reported high levels of ‘burn-out’ among community mental health team (CMHT) staff, although paradoxically associated with relatively good job satisfaction (Fagin et al , 1995; Prosser et al , 1996; Onyett et al , 1997; Wykes et al , 1997). Some authors have argued that staff delivering intensive community care to severely ill client groups are very susceptible to burn-out, threatening the sustainability of this model (Dedman, 1993; Connolly et al , 1996). However, assertive outreach team staff may also find the work particularly rewarding.…”
mentioning
confidence: 99%
“…Outflow control, i.e., control of discharge, is important for MCHT to do its job of decreasing bed usage. In the Connolly, Marks, Lawrence, McNamee, and Muijen, (1996) Southwark, London, study in Chapter 1, it was shown that when the MCHT service lost control of the discharge decision making, the length of stay increased by 300%.…”
Section: Factors That Control the Flow Of Patients Out Of The Hospitamentioning
confidence: 99%
“…Tuttavia, la prosecuzione dello studio per un periodo di 4 anni ha evidenziato che i vantaggi in termini di costo-efficacia del DLP, rispetto al trattamento standard ospedaliero, tendevano a ridursi progressivamente fino a scomparire al termine del quarto anno (Knapp et al, 1998). Alcune osservazioni sulle problematiche emerse nella prosecuzione di lungo termine del programma al Maudsley Hospital sono state recentemente presentate (Connolly et al, 1996).…”
Section: Epidemiologia E Psichiatria Sociale 7 3 1998unclassified